2012
DOI: 10.1002/pbc.24244
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of pemetrexed in children and adolescents with refractory solid tumors: A Children's Oncology Group study

Abstract: Background Pemetrexed is a multi-targeted antifolate that inhibits key enzymes involved in nucleotide biosynthesis. We performed a phase 2 trial of pemetrexed in children with refractory or recurrent solid tumors, including CNS tumors, to estimate the response rate and further define its toxicity profile. Procedure Pemetrexed, at a dose of 1910 mg/m2, was administered as a 10-minute intravenous infusion every 21 days. Patients also received vitamin B12, daily multivitamin supplementation, and dexamethasone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Although the anti-folate agents methotrexate and 5-fluorouracil have been widely used for decades in the treatment of malignant tumors, pemetrexed is a relatively new therapeutic agent currently approved as a first line treatment for mesothelioma (Dowell et al, 2012), NSCLC in association with platinum-based chemotherapy (Mubarak et al, 2012), and in newly diagnosed brain metastasis (Bailon et al, 2012). It also showed clinical activity in other adult tumors such as breast, colorectal, bladder, cervical, gastric and pancreatic cancers (Adjei, 2004; Chattopadhyay et al, 2007; Warwick et al, 2013). Genes regulating pyrimidine metabolism were also enriched in mouse G3 MBs compared with mouse GNPs and SHH MBs, in agreement with the anti-proliferation effects of gemcitabine, a pyrimidine cytidine analogue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the anti-folate agents methotrexate and 5-fluorouracil have been widely used for decades in the treatment of malignant tumors, pemetrexed is a relatively new therapeutic agent currently approved as a first line treatment for mesothelioma (Dowell et al, 2012), NSCLC in association with platinum-based chemotherapy (Mubarak et al, 2012), and in newly diagnosed brain metastasis (Bailon et al, 2012). It also showed clinical activity in other adult tumors such as breast, colorectal, bladder, cervical, gastric and pancreatic cancers (Adjei, 2004; Chattopadhyay et al, 2007; Warwick et al, 2013). Genes regulating pyrimidine metabolism were also enriched in mouse G3 MBs compared with mouse GNPs and SHH MBs, in agreement with the anti-proliferation effects of gemcitabine, a pyrimidine cytidine analogue.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for lymphomas, leukemias [27,29] and nonsmall-cell lung carcinoma [34,45] . Nevertheless, chemotherapy regimens with pemetrexed were not effective for pediatric patients with medulloblastomas, ependymomas and high-grade gliomas [49] , and the addition of methotrexate in the chemotherapeutic treatment of infratentorial ependymomas did not improve the response to these drugs [50] . However, none of these studies assessed MTAP expression in the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though PMX was less toxic, it did not induce apoptosis more effectively than MTX in OS cell lines in vitro [80]. In the same vein, a phase II study of PMX conducted in patients with high-grade, advanced, or refractory osteosarcoma to assess response rate and toxicity (NCT00523419) showed that PMX was well-tolerated but did not enhance anti-tumor activity [81,82]. …”
Section: Current Therapiesmentioning
confidence: 99%